1997
DOI: 10.1002/hep.510250419
|View full text |Cite
|
Sign up to set email alerts
|

The role of insulin-like growth factor II in the malignant transformation of rat liver oval cells

Abstract: (IGF II), transforming growth factor a, and hepatocyte Oval cells are small nonparenchymal epithelial cells growth factor. that first appear in the periportal areas of the liver and IGF II, a polypeptide of 67 amino acids, is structurally thereafter invade the whole parenchyma when mice or related to proinsulin. 1,2 It can bind specifically and with high rats are exposed to a variety of chemical carcinogens.affinity to two structurally unrelated receptors, the type 1 In the present study we have analyzed the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…These ®ndings are perfectly in line with a previous report by Serrano et al [31], who showed that the expression of oncogenic ras in primary human cells results in a permanent G1 arrest, this arrest being phenotypically indistinguishable from cellular senescence. For the aim of this study the rat liver epithelial cell line OC/CDE 22 was chosen, since it had successfully been used in the past to analyze the involvement of p53 [32], insulin-like growth factor II [33], and Ha-ras [32,34] in the malignant transformation of liver cells.…”
Section: Discussionmentioning
confidence: 99%
“…These ®ndings are perfectly in line with a previous report by Serrano et al [31], who showed that the expression of oncogenic ras in primary human cells results in a permanent G1 arrest, this arrest being phenotypically indistinguishable from cellular senescence. For the aim of this study the rat liver epithelial cell line OC/CDE 22 was chosen, since it had successfully been used in the past to analyze the involvement of p53 [32], insulin-like growth factor II [33], and Ha-ras [32,34] in the malignant transformation of liver cells.…”
Section: Discussionmentioning
confidence: 99%
“…The mitogenic action of IGF2 is generally thought to function through cross reaction with IGFI receptors and IGFI receptors are not detectable in liver (Rotwein and Hall, 1990). However, IGFI receptors have been detected in malignantly transformed liver cells which overexpress IGF2 (Zhang et al, 1997). The liver is also a rich source of insulin receptors and the insulin signaling molecule, Insulin Receptor Substrate-1, (IRS-1) (Furusaka et al, 1994;Tanaka and Wands, 1996a,b;Nishiyama and Wands, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…IGF-II has been shown to induce proliferation of malignantly transformed liver oval cells (M22 cells) via an autocrine mechanism when binding to IGF-IR in vitro; however, transfection of an IGF-II complementary DNA into normal oval cells (OC/CDE 22 cells) does not cause a malignant transformation. (173) This finding suggests that IGF-II may only exert mitogenic effect on malignant liver oval cells themselves. Additionally, proliferation and differentiation of liver oval cells can be negatively regulated by IGFBP-3 via TGF-beta pathway both in vivo and in vitro, suggesting that decreased IGFBP-3 may potentiate aberrant proliferation of oval cells.…”
Section: Role Of Liver Stem Cells In Obesity Related Hccmentioning
confidence: 99%